TERTIARY STUDENTS’ READING INTEREST AND CRITICAL THINKING SKILL: A CORRELATIONAL - Wina Fanta Anggalya; Rahma Dianti (Language and Education Journal, 2023)
Many research have proved that reading interest can influence the way someone thinks. It is crucial to promote critical thinking skills in higher education level. This study aimed to find out the level of students’ critical thinking skills and to reveal the association between reading interest and critical thinking skill. This study used correlational research design. Fiftyseven tertiary students of English Education Department at Tridinanti University participated as the sample which were selected by using total sampling technique since the population size was small. The data were collected by administering a questionnaire of reading interest and critical thinking test. After gathering the data, it was analyzed by using Pearson Product Moment to examine the association between the students’ reading interest and their critical thinking skill. The data obtained were analyzed by using Pearson Product Moment. The result of correlational analysis revealed that there was a very weak correlation between reading interest and critical thinking skill